2016
DOI: 10.5604/17331331.1204761
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ureB Sequence Diversity, Urease Activity and Genotypic Variations of Different Helicobacter pylori Strains in Patients with Gastric Disorders

Abstract: A b s t r a c tAssociation of the severity of Helicobacter pylori induced diseases with virulence entity of the colonized strains was proven in some studies. Urease has been demonstrated as a potent virulence factor for H. pylori. The main aim of this study was investigation of the relationships of ureB sequence diversity, urease activity and virulence genotypes of different H. pylori strains with histopathological changes of gastric tissue in infected patients suffering from different gastric disorders. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Moreover, urease and catalase activity, as well as protein synthesis by H. pylori , might be impaired at very low pH [ 27 ]. Greater urease activity might be associated with a higher risk of induction of the histopathological alterations within the gastric mucosa and further gastric carcinogenesis [ 28 ]. Urease activity might be modulated by the flbA gene, the same gene that is involved in flagellar biosynthesis [ 29 ].…”
Section: Ureasementioning
confidence: 99%
“…Moreover, urease and catalase activity, as well as protein synthesis by H. pylori , might be impaired at very low pH [ 27 ]. Greater urease activity might be associated with a higher risk of induction of the histopathological alterations within the gastric mucosa and further gastric carcinogenesis [ 28 ]. Urease activity might be modulated by the flbA gene, the same gene that is involved in flagellar biosynthesis [ 29 ].…”
Section: Ureasementioning
confidence: 99%
“…Up to now, more than 30 species have been characterized and well-recognized by microbiologists. H. pylori is the most recognized bacterium associated with dyspepsia in humans [1][2][3][4]. However, NHPGH species with typical spiral morphology has the ability to colonize the stomach of humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…According to the report by Ghalehnoei et al, some variants of UreB could be shown depending on the strains (17). Thirty percent of patients with intestinal metaplasia showed a single amino acid sequence change in UreB, but this change did not affect the urease activity at all (17). As mentioned above, urease is a relatively conserved protein for H. pylori survival in stomach, and although it may have some changes depending on the strains, it does not seem to affect the function and activity of urease.…”
Section: Journal Of Bacteriology and Virologymentioning
confidence: 97%
“…Urease, which hydrolyzes urea into NH3 and CO2, plays important role in H. pylori colonization in the acidic condition of stomach (pH 3) (10). According to the report by Ghalehnoei et al, some variants of UreB could be shown depending on the strains (17). Thirty percent of patients with intestinal metaplasia showed a single amino acid sequence change in UreB, but this change did not affect the urease activity at all (17).…”
Section: Journal Of Bacteriology and Virologymentioning
confidence: 97%